Novel RANKL DE‐loop mutants antagonize RANK‐mediated osteoclastogenesis. (7th July 2017) - Wang, Yizhou; van Assen, Aart H.G.; Reis, Carlos R.; Setroikromo, Rita; van Merkerk, Ronald; Boersma, Ykelien L.; Cool, Robbert H.; Quax, Wim J.
Abstract : Bone is a dynamic tissue that is maintained by continuous renewal. An imbalance in bone resorption and bone formation can lead to a range of disorders, such as osteoporosis. The receptor activator of NF‐κB (RANK)–RANK‐ligand (RANKL) pathway plays a major role in bone remodeling. Here, we investigated the effect of mutations at position I248 in the DE‐loop of murine RANKL on the interaction of RANKL with RANK, and subsequent activation of osteoclastogenesis. Two single mutants, RANKL I248Y and I248K, were found to maintain binding and have the ability to reduce wild‐type RANKL‐induced osteoclastogenesis. The generation of RANK‐antagonists is a promising strategy for the exploration of new therapeutics against osteoporosis. Abstract : The RANK–RANK‐ligand pathway plays a major role in bone remodeling. In this study, we investigated the effect of mutations at position I248 in the DE‐loop of murine RANKL on its interaction with RANK. RANKL I248Y and I248K were found to antagonize wild‐type RANKL‐induced osteoclastogenesis, thus providing a promising strategy for the exploration of new therapeutics against osteoporosis.